Identification of different inks using ft -ir - Saidin, Mohd Hilmi (Universiti Sains Malaysia, 2006)
Infrared spectroscopy is one of the powerful techniques used in the characterization of materials. The vast majority of the molecules in universe possess vibration energy within the mid-infrared region, which extends from 4000-400 cm·1 , so it is defined as fingerprint region for most of the materials particularly those polymeric materials that incorporate chemical functional groups as part of their structure. In this project, three types of inks were used for analysis of the components: ballpoint inks, marker pen inks and fountain inks. Each type has different brands and color. The focus of this study was to assign the major absorption bands and try to differentiate the types of inks. This aspect of studies is important from the forensic point of view. On the basic of spectral bands, the fountain pen, ballpoint pen and marker pen inks, were easily identified and discriminated; mainly the dyes components